2022
DOI: 10.3847/1538-3881/ac8154
|View full text |Cite|
|
Sign up to set email alerts
|

TESS Hunt for Young and Maturing Exoplanets (THYME). VII. Membership, Rotation, and Lithium in the Young Cluster Group-X and a New Young Exoplanet

Abstract: The public, all-sky surveys Gaia and TESS provide the ability to identify new young associations and determine their ages. These associations enable study of planetary evolution by providing new opportunities to discover young exoplanets. A young association was recently identified by Tang et al. and Fürnkranz et al. using astrometry from Gaia (called “Group-X” by the former). In this work, we investigate the age and membership of this association, and we validate the exoplanet TOI 2048 b, which was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 154 publications
1
11
0
Order By: Relevance
“…The top plot of Figure 6 shows the rotation period of TOI-4562 compared with stars of known nearby clusters and associations. TOI-4562's P å is consistent with that of stars belonging to Group X (Messina et al 2022;Newton et al 2022), with an estimated age of 300 Myr.…”
Section: Stellar Rotation and Gyrochronologysupporting
confidence: 55%
“…The top plot of Figure 6 shows the rotation period of TOI-4562 compared with stars of known nearby clusters and associations. TOI-4562's P å is consistent with that of stars belonging to Group X (Messina et al 2022;Newton et al 2022), with an estimated age of 300 Myr.…”
Section: Stellar Rotation and Gyrochronologysupporting
confidence: 55%
“…PDCSAP flux is effective at removing long-term trends. Newton et al (2022) find that PDCSAP could also effect the observed rotation signature in some sectors; comparison of the SAP and PDCSAP light curves for stars in our sample indicates this is not a concern for us. Thus, for this paper we use the PDCSAP flux.…”
Section: Optical Photometric Datamentioning
confidence: 55%
“…The closest case is MELANGE-1, which is closer in age (∼250 Myr; Tofflemire et al 2021) and hence has similar large V off scatters. Most of the stars in MELANGE-2 (Newton et al 2022) and MELANGE-3 (Barber et al 2022) that agree in RV space are within 1-2 km s −1 in V off .…”
Section: A Potential ∼200 Myr Young Association Candidate In the Phoe...mentioning
confidence: 80%
“…Similarly, the Pleiades, Hyades, and Praesepe clusters are shown for comparison. We add the P ROT distribution of Group X members (∼300 Myr, Newton et al 2022). The left panel shows all RV comoving candidates where P ROT are derived.…”
Section: Stellar Rotational Periodmentioning
confidence: 99%
See 1 more Smart Citation